Molecular Detection of Staphylococcal Enterotoxins and mecA Genes Products in Selected Food Samples Collected from Different Areas in Khartoum State - Mohammed Yahya Ahmed; Hashim Abdalbagi Ali; Babbiker Mohammed Taher Gorish; Sara Omer Ali; Eman Saif Aldein Abdalrhim; Mawada Hamza Mergani; Asmaa Abass Abd Elgadir; Somaya Khalid Mohammed; Salma Omer Ahmed; Naglaa Alsaeid Musa; Alaa Saeed Ahmed; Wafaa Mohammed Abdalla; et al. (International Journal of Microbiology)
Staphylococcal food poisoning is an intoxication that results from the consumption of improperly prepared or stored foods containing sufficient amounts of one or more preformed S. aureus enterotoxins. Nowadays, many researchers worldwide noted an emergence of resistant strains such as Staphylococci particularly for the antibiotic methicillin. Therefore, this study was aimed to determine the existence of Staphylococcus aureus and its enterotoxins, mecA genes, in selected food samples. A total of 400 selected food samples were collected from different areas in Khartoum State. The selected foods included cheese, meat products, fish, and raw milk. One hundred samples from each type of food were cultivated, and the resultant growth yielded 137 (34.25%) S. aureus, 126 (31.5%) bacteria other than S. aureus, and 137 (34.25%) yielded no growth. Eighty-four of the 137 S. aureus isolates were randomly selected and tested for the presence of mecA and enterotoxin genes. The oxacillin sensitivity test showed that 15 (11%) of 137 S. aureus isolates were oxacillin resistant. The PCR assay showed that the mecA gene was detected in 15 of 84 (17%) S. aureus isolates. Simultaneously, only 2 (2.385%) out of 84 S. aureus isolates showed an enterotoxin B gene product. There was a relatively moderate prevalence of methicillin-resistant Staphylococcus aureus with very low frequency of enterotoxin B gene in different kinds of selected food samples collected from Khartoum State. These findings elucidate the increased risk on public in Khartoum being affected by Staphylococcal food poisoning upon consumption of dairy or meat products prepared in unhygienic conditions that could lead to intoxication by Staphylococcus aureus enterotoxins.